DAYA TARIK KAWASAN SOSROWIJAYAN, YOGYAKARTA SEBAGAI KAMPUNG WISATA BAGI WISATAWAN MANCANEGARA - Riska Ardelia Permatasari; Hadi Wahyono (Diponegoro University, 2017)
As a tourist city, Yogyakarta has several areas that can become an attraction for international tourists, such as the Sosrowijayan. This area is located in a strategic location with a wide range of accommodation for international tourists. The attractiveness of this area particularly for the international tourists is based on its unique characteristics that have not explored in the previous research. Hence, this research aims to determine the level of attraction and the factors that influence the attractiveness of this area based on the perception of international tourists. This research applied quantitative research methods with questioner in the data collection to examine the tourist perception on the variables of destination attractiveness. This research found that these main factors are comfortability, relaxation, accommodation services, and accessibility.